2021
DOI: 10.3390/vaccines9060662
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy and Its Associated Factors in Japan

Abstract: The vaccine confidence index in Japan is one of the lowest worldwide. This study aimed to examine the proportion of COVID-19 vaccine hesitancy in the Japanese population using a larger sample and more robust statistical methods than previously, and to identify factors associated with vaccine hesitancy. We conducted a nationwide, cross-sectional Internet survey on 8–26 February 2021, and calculated the proportion and odds ratios for vaccine hesitancy. Among 23,142 responses analyzed, the proportion of COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
146
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(174 citation statements)
references
References 25 publications
21
146
7
Order By: Relevance
“…Women, older adults, people with a high educational level, and people who had lost a family member or a friend due to COVID-19 were more likely to hesitate to be vaccinated. These characteristics differ from studies carried out in developed countries [39,40] and reinforce that, although VH is a global problem, specificities of different population groups must be considered and understood.…”
Section: Discussioncontrasting
confidence: 70%
“…Women, older adults, people with a high educational level, and people who had lost a family member or a friend due to COVID-19 were more likely to hesitate to be vaccinated. These characteristics differ from studies carried out in developed countries [39,40] and reinforce that, although VH is a global problem, specificities of different population groups must be considered and understood.…”
Section: Discussioncontrasting
confidence: 70%
“…The questionnaire used in this study was self-developed following a review of the literature [22][23][24][25][26][27][28][29][30][31][32][33][34] and agreement among experts. The questionnaire was structured into four sections covering sociodemographic data, medical history, COVID-19 pandemic-related information, and COVID-19 vaccine-related information.…”
Section: Questionnairementioning
confidence: 99%
“…Globally, there have been a large number of studies within a limited time on COVID-19 vaccine hesitancy among younger adults [ 4 , 5 , 9 , 10 , 19 , 20 ], including some with evidence of vaccine hesitancy among younger people in Japan [ 21 , 22 , 23 , 24 ]. Although these studies demonstrated higher vaccine hesitancy among younger adults in Japan, the magnitudes of hesitancy were somewhat different, possibly due to differences in the timing of data collection and definitions of vaccine hesitancy.…”
Section: Introductionmentioning
confidence: 99%
“…Yoda and Katsuyama [ 22 ] and Machida et al [ 23 ] found the hesitancy rate in Japan during the trial phase of the vaccination program to be 34.3% and 37.9%, respectively. Kadoya et al [ 21 ] found the rate to be 53%; Okubo et al [ 24 ] found the rate to be 11% after the rollout of the vaccination program. Despite differences in vaccine hesitancy at different stages of the vaccination program, previous studies have provided consistent evidence related to gender and age associations with vaccine hesitancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation